Exploring The Spatial Mechanism of Income Generation Space in Oyster Seeker Village, Banda Aceh - Putri, Aji Sofiana; Fadhil, Muhammad Naufal (Universitas Muhammadiyah Surakarta, 2025)
The oyster seeker community in Alue Naga relies on the coastal environment for finding, cultivating, harvesting, processing, and selling oysters. The spatial dynamics of interaction among humans, oysters, and the coastal environment that generates income for the oyster-seeking community remains thoroughly underexplored. This study investigates the spatial mechanisms of income-generating spaces created by oyster seeker activities in Alue Naga, Banda Aceh, Indonesia. The research aims to explore the spatial patterns formed by the activities and practices of oyster seekers that contribute to their daily income. This study employs a design-driven research method, utilising a qualitative approach shaped by design thinking, spatial sensitivity, and a thorough architectural understanding using meaning from interviews and on-site observations. The research indicates that income-generating activities in Alue Naga oyster seeker village are established through three different spatial mechanisms: 1) the utilisation of land and water border areas, 2) the use of time and domestic space as components in the income-generating process, and 3) social aspects as the engine of spatial mechanism to generate income. This research also reveals that coastal environments can generate spatial mechanisms that shape income-generating spaces for coastal communities, which should be considered when designing spaces, architecture, and urban contexts.